Diabetes in Ramadhan: an innovative guide to fasting wisely for people with diabetes / Fatimah Zaherah Mohamed Shah ... [et al.] - Mohamed Shah, Fatimah Zaherah; Eddy Warman, Nur 'Aini; Awang, Mohd Hazriq; Mohamed, Aimi Fadilah; Zainordin, Nur Aisyah; Abdul Ghani, Rohana (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The incidence of Type 2 Diabetes Mellitus (DM) in Malaysia is increasing, with 59% in Malays followed by the other races. Fasting in Ramadhan for those with DM is challenging and needs close monitoring with sufficient and comprehensive medical advice. Diabetic complications during fasting is mainly seen in patients with improper disease control or inadequate information. This guide aims to facilitate knowledge attainment and improve dissemination of information to mitigate the risk of complications in Ramadhan and to pave the way to fasting safely. Innovation product. A novel guidebook fashioned for educating people with DM and their care-givers on the proper approach to fasting safely in Ramadhan. A compilation of important information on managing the challenges DM patients face in the fasting month was assembled, gathered mainly from the Malaysian DM clinical practice guidelines and the International Diabetes Federation (IDF) Diabetes in Ramadan Guideline. This compendium was designed primarily in the Malay language to enable better understanding in the Malaysian population. This guide detailed essential knowledge on fasting in Ramadhan for people with DM, and was divided into a few categories, comprising of: risks and possible complications of fasting in people with DM, population categories at high risk for continuous fasting, adequate and timing of blood sugar monitoring, when to break of fast in the event of complication and steps to handle the situation, medication adjustment, dietary advice and tips on keeping active during the fasting month. Conclusion. A practical tool that is simplified for general use is essential in empowering people with diabetes to handle to their condition better and to facilitate safe fasting in the month of Ramadhan. This guide has been designed to fulfil this requirement and aspires to be beneficial in clinical practice and additionally function as a valuable instrument for personal and public use.